Expression of functional diphtheria toxin receptors on highly toxin-sensitive mouse cells that specifically bind radioiodinated toxin. - Naglich, J G (1992)
Diphtheria toxin (DT), a bacterial protein exotoxin, inactivates mammalian cell elongation factor 2 after toxin internalization by receptor-mediated endocytosis. To isolate the DT receptor, we cotransfected DT-resistant wild-type mouse L-M cells with a cDNA library constructed from RNA of highly toxin-sensitive monkey Vero cells and with a neomycin-resistance gene. Stably transfected G418-resistant L-M colonies were screened for DT sensitivity in a replica plate assay. After screening of 8000 colonies, one DT-sensitive (DTS) colony was isolated. The purified DTS mouse cells are highly toxin-sensitive; they are at least 1000-fold more sensitive than wild-type L-M cells and only approximately 10-fold less sensitive than Vero cells. Incubation of the DTS mouse cells with CRM 197, a nontoxic form of DT that competitively inhibits the binding of native DT to the toxin receptor, protected them from DT-mediated toxicity. More important, these DTS mouse cells express receptors on their cell surface that bind radioiodinated DT in a specific fashion, a property hitherto readily demonstrable only with highly toxin-sensitive cells of monkey origin. Furthermore, HA6DT, a DT fragment comprising the Mr 6000 carboxyl-terminal receptor-binding domain, inhibited the binding of radioiodinated toxin to these DTS mouse cells to the same extent as unlabeled DT. With these DTS mouse cells as a source of monkey cDNA, it should be possible to clone the gene encoding the DT receptor.